The genus Thrips (Thysanoptera, Thripidae) in Australia, New Caledonia and New Zealand - Mound, Laurence A.; Masumoto, Masami (Zootaxa, 2005)
The genus Thrips includes about 280 species worldwide. An identification key is provided to 41 from the Australian Region. Of these, 33 (including 7 new species) are recorded from Australia, 5 (including 1 new species) are known only from New Zealand, and 3 (including 1 new species) are known only from New Caledonia. Two species-groups are defined: the “Thrips obscuratus speciesgroup” comprising 8 species from New Caledonia and New Zealand, and the “Thrips seticollis species-group” comprising 6 species from the southern half of Australia. A further group, the “Thrips orientalis species-group” involves 12 species in South East Asia, and four of these are recorded from Australia. In the temperate areas of this continent there are 5 species that are clearly introduced subsequent to European settlement. From Australia’s northern tropical area 18 species are recorded here, but as most of these are known also from Asian or Pacific territories some may have been introduced either through human activities or naturally on winds. The Australian Plague Thrips is recognised as comprising two species, the essentially southern T. imaginis and a closely related new species, T. safrus, usually north of Latitude 27º. For all 41 species host-plant and distribution details are included, as well as morphological diagnoses.